Erythrocyte Catalase Activities in Alcohol Consumption, Medications and Some Diseases (Annals of Medical Research, 2021)
None
Keywords: Catalase - Red Blood Cell - Leukemia - Cardiac Disease – Hepatitis - Diabetes Mellitus